Towards the Synthesis of the Unusual Monosaccharides Found in the Shigella sonnei O-Antigen and Analysis of Shigella flexneri 2a Glycoconjugate Vaccine Samples - Anderson, Taigh Byrne (Department of Chemistry, 2021)
Shigellosis (bacillary dysentery) is a severe inflammatory diarrhoeal disease in humans caused by the Gram-negative bacteria belonging to the Shigella species. Despite over 60 years of vaccine research, no licensed vaccine to prevent shigellosis is commercially available. Bioconjugate vaccines based on the O-antigen against various Shigella serotypes are under development. Shigella sonnei and Shigella flexneri 2a are the most prevalent serotypes in industrialised and developed countries respectively and is the subject of this study. This project involves the design and evaluation of alternative synthetic routes to derivatives of 2-acetamido-4-amino-2,4,6-trideoxy-β-D-galactopyranose (FucNAc4N/AAT) and 2-acetamido2-deoxy-α-L-altruronic acid (AltNAcA), the two unusual monosaccharides found in the repeating unit of the Shigella sonnei O-antigen. Since these sugars are not commercially available, synthetic derivatives are required as authentic standards for the analysis of the bioconjugate. Various routes to the FucNAc4N derivative were investigated and evaluated. Routes proceeding either through 1,6-anhydro-D-glucose or cyclohexyl-2-acetamido-1-thioglucoside were shown to have potential, but ultimately both were rejected on the basis of inefficient conversions in the early stages of the synthetic sequence. However, important insights were gained into the crucial challenge of differentiating O-3 and O-4, common to any approach involving starting materials with the D-gluco configuration. This led to preparation in good yield of phenyl 2-amino-2-N,3-Ocarbonyl-2-deoxy-1-thio-β-D-glucopyranoside as a key oxazolidinone-protected intermediate, which allowed for successful preparation of a FucNAc4N derivative in the form of a 4-azido-βthioglycoside. This was achieved in 10 steps from the commercially available 2-acetamido1,3,4,6-tetra-O-acetyl-β-D-glucopyranose in an overall yield of 17%. Synthesis of an AltNAcA derivative was initially investigated via a sequence starting from a glucofuranurono-3,6-lactone. This involved initial inversion at C-5 followed by opening of the lactone and migration of the substituent at O-5 to O-3, to form an idofuranuronate which, however, could not be readily converted to the required pyranose form. A more successful route utilized a 6-iodo-2,3-oxazolidinone derivative of D-glucose, prepared as a key intermediate in the synthesis of FucNAc4N. The crucial epimerization at C-5 was attempted through initial formation of the 5-ene, followed by a hydroboration/oxidation, but this led exclusively to the Drather than the L-sugar. Computer modelling and literature precedent suggested that the anomeric configuration strongly influenced the face selectivity of the hydroboration step. An αanalogue of the 6-iodo-2,3-oxazolidinone derivative was therefore prepared via an efficient Lewis acid catalysed anomerization of a β-thioglucoside. However attempts to carry out a base- iii mediated elimination to the corresponding 5-enopyranoside were not successful, giving rise instead to a product in which the oxazolidinone had been cleaved followed by intramolecular substitution of the 6-iodide to form a 3,6-anhydro derivative. On the basis of these results and observations, an alternative synthetic route to AltNAcA has been proposed, which incorporates early formation of an α-glycoside and removal of the useful 2,3-oxazolidinone protecting group, thus setting the substrate up for effective elimination followed by selective hydroboration from the less hindered β-face to give the L-sugar. This study also incorporates a spectroscopic analysis of Shigella flexneri 2a glycoconjugate and glycopeptide samples. A full set of nuclear magnetic resonance (NMR) spectra were recorded and analysed, resulting in the unambiguous determination of the structure and integrity of the O-antigen saccharide component.